ANALISIS KOMUNIKASI SOSIAL DALAM PENYELESAIAN KONFLIK SENGKETA LAHAN ADAT SUKU KAJANG AMMATOA - Asrul Anas,; Andi Alimuddin Unde,; Tuti Bahfiarti, (Jurnal Dakwah Tabligh, 2023)
This study aims to analyze social communication in resolving conflict over customary land disputes of the Kajang Ammatoa tribe. The approach used is a qualitative descriptive approach. Retrieval of data used through (in-depth interviews, observation, and documentation). Retrieval of research informants using purposive sampling. Data analysis used the Miles and Huberman analysis method with data reduction, data collection, data presentation, and conclusion drawing steps. The results of this study indicate that the analysis of communication in the resolution of the Kajang Ammatoa customary land dispute conflict wants mediation according to customary law to resolve issues with PT. PP London Sumatra which is considered to have seized the land of the indigenous people of the Kajang tribe. PT. PP London Sumatra still adheres to the HGU granted by the government and considers that conflicts that occur should be carried out by law.